Synthesis and Characterization of Complexes of Some Bivalent Metal Ions with Omeprazole - DAS, SUPRIYA; MALIK, SUMAN; JAIN, BHARTI; MORE, JAISHREE (Asian Journal of Chemistry, 2010)
The Hg(II) and Mn(II) complexes have been synthesized with 5-methoxy-2-[(4-methoxy-3,5-dimethyl-2-pyridinyl)methyl sulfinyl]- 1H-benzimidazole (omeprazole). Omeprazole is a proton pump inhibitor (PPI). Analytical data and stochiometry suggest ligand metal ratio of 2:1 for both Hg(II) and Mn(II) complexes. The ligand behaves as a bidentate N, O donors. The complexes have been synthesized and characterized by elemental analysis, magnetic susceptibility and infrared spectrum studies. The complexes have been formulated as (C17H19N3O3S)2Hg and (C17H19N3O3S)2Mn·2H2O.